(untitled) (Revista Ciência Agronômica, 2015)
Applying micronutrients together with the herbicides used in plant desiccation can ensure an adequate supply of these nutrients and a reduction in production costs under a direct seeding (DSS) system. The aim of this study was to evaluate the effect of dosages of molybdenum (Mo), applied both in a desiccation operation together with glyphosate on the straw of brachiaria (Brachiaria brizantha) and separately via the leaves, on the common bean (cultivar Ouro Vermelho) grown under DSS. A randomised block design was used with four replications in an arrangement of sublots. In the lots, dosages of Mo (0, 0.1, 0.2, 0.4 and 0.8 kg ha-1) were applied together with the desiccant herbicide (glyphosate), and in the sublots, two dosages of Mo (0 and 100 g ha-1) were applied via the leaves. Two experiments were carried out in the town of Coimbra, in the state of Minas Gerais, Brazil, one in 2009 and the other in 2010 (the same treatments having been applied in the experimental area in 2008). Foliar fertilization was carried out with sodium molybdate [(Na2MoO4 ) (39% Mo)] at stage V4 in the bean plants. The application of Mo, whether mixed with the desiccant or applied via the leaves, had no significant effect on yield components or on productivity. Levels of Mo and N in the grain, and of N in the leaves, increased with the application of Mo, both when mixed with the desiccant and applied via the leaves.